PENGARUH PRILAKU NASABAH DAN KARAKTER INDIVIDU TERHADAP PENGAJUAN KREDIT DI PT. BPR DURIAN MANDIRI KOTA SAWAHLUNTO - Zakiyah, Dzikra; Yeni, Afni; Arfimasri, Arfimasri (Ekonis: Jurnal Ekonomi dan Bisnis, 2024)
Abstract: This study aims to analyze the influence of customer behavior and individual character on credit applications at PT. BPR Durian Mandiri Sawahlunto City. The sample in this study were 50 respondents with accidental sampling method. Based on the results of multiple linear regression analysis of the variables of Customer Behavior and Individual Character on Credit Submission with a value of Y = 24.613 + 0.052 (X1) + 0.458 (X2) + e. From the t test conducted on the variable X1 + 0.052 (X1) + 0.458 (X2) + e. From the t test conducted on variable X1, namely Customer Behavior with a t-count value greater than the t-table 2.276 2.012, which means that the Customer Behavior variable affects Credit Submission, as for variable X2, namely Individual Character, the t-count value is greater than the t-table 2.391 2.012, which means that Individual Character affects Credit Submission. While the results of the f-test analysis obtained an f-count value greater than the f-table, namely 3.523 3.19, which means that Customer Behavior and Individual Character together have an effect on Credit Submission.Keyword : Customer Behavior, Individual Character, Credit Application.